Shaping the future through standardization - Jakobs, Kai 1957- (IGI Global, Engineering Science Reference, 2020)
"This book examines quality and standardization within diverse organizations globally with a special focus on future perspectives, including how standards and standardization may shape the future"--
Keywords: Standardization